Kesiapsiagaan Perawat Rumah Sakit Terhadap Bencana: Scoping Review - Sinaga, Freda Mai; Trisyani, Yanny; Emaliyawati, Etika (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Disaster preparedness among hospital nurses is crucial in disaster response, impacting the capacity of healthcare services in emergency situations. This study aims to identify the forms of disaster preparedness among nurses, assess the level of preparedness, and identify the factors influencing it. This study uses a literature review based on the framework by Arksey and O’Malley, with literature searches conducted through EBSCO host-CINAHL Plus and Scopus using relevant keywords. Articles were selected based on inclusion criteria and analyzed using a data mapping table. From 16 analyzed articles (13 quantitative, 3 qualitative, 2013-2023), it was found that disaster preparedness among nurses is generally moderate to low. Forms of preparedness include knowledge, attitude, skills, self-preparedness, crisis management, perception, and operational competence. Disaster preparedness is influenced by demographic factors, training experience, psychological conditions, and hospital infrastructure. This study highlights the importance of a multi-faceted approach to improving disaster preparedness among hospital nurses. Keywords: Disaster Preparedness, Hospital, Nurse.  ABSTRAK Kesiapsiagaan bencana pada perawat di Rumah sakit adalah kunci dalam respons bencana, yang juga mempengaruhi kemampuan layanan kesehatan dalam situasi darurat. Penelitian ini bertujuan untuk mengidentifikasi bentuk kesiapsiagaan bencana pada perawat, menilai tingkat kesiapsiagaan, dan mengidentifikasi faktor-faktor yang mempengaruhinya. Penelitian ini menggunakan scoping review berdasarkan framework Arskey dan O’Malley, dengan pencarian literatur melalui EBSCO host-CINAHL Plus dan Scopus menggunakan kata kunci terkait. Artikel dipilih berdasarkan kriteria inklusi dan dianalisis dengan tabel pemetaan data. Dari 16 artikel yang dianalisis (13 kuantitatif, 3 kualitatif, 2013-2023), ditemukan bahwa kesiapsiagaan bencana pada perawat umumnya sedang hingga rendah. Bentuk kesiapsiagaan mencakup pengetahuan, sikap, keterampilan, kesiapan diri, manajemen krisis, persepsi, dan kompetensi operasional. Kesiapsiagaan bencana dipengaruhi oleh faktor demografi, pengalaman pelatihan, kondisi psikologis, dan fasilitas infrastruktur. Penelitian ini menekankan pentingnya pendekatan multi-faset untuk meningkatkan kesiapsiagaan bencana di kalangan perawat rumah sakit. Kata Kunci: Kesiapsiagaan bencana, Rumah sakit, Perawat